Design and Implementation of Integrated Digital Infrastructure to Support Smart Campus: Case Study of Building E of Sari Mulia University - Kurniawan, Muhamad; Mikhael Neta Yahu; Erwenda Tri Hapsari; Adella Adriani (LPPM Universitas Sari Mulia, 2025)
The rapid growth of information technology has forced universities to develop an integrated, reliable, and secure digital infrastructure to support academic and administrative activities. This research discusses the design and implementation of Integrated Digital System Infrastructure (ISDT) in Building E of Sari Mulia University as a prototype for the development of Smart Campuses. This research adopts a structured and sequential implementation methodology, ranging from needs analysis, field surveys, system architecture design, procurement, deployment of physical infrastructure, device installation, network configuration and security, to comprehensive testing and post-implementation monitoring. The infrastructure deployed includes fiber optic backbones, VLAN-based network segmentation, Layer 3 switching, Wi-Fi 6 access points, enterprise servers, mini-data centers, and integrated monitoring and security systems. The results of the study show that the implementation of ISDT successfully provides stable connectivity, improved network performance, centralized system management, and improved security. The study shows that a systematic implementation approach can effectively support the integration and scalability of digital services, and can serve as a reference model for the development of similar infrastructure in other university buildings.